Characterization of murine mammary stem/progenitor cells in a D-galactose-induced aging model - Gao, Hui (Aging (Albany NY), 2021)
Aging plays an important role in many diseases, including breast cancer. Aged mammary stem/progenitor cells are perceived to be the cells of origin in breast tumorigenesis; however, the extensive use of mice who have aged naturally for research is hampered by cost, time, disease complications, and high mortality. In this study, we characterized murine mammary stem/progenitor cells in a D-galactose-induced accelerated aging model and compared them with findings from our earlier study on mice from natural aging. Our results showed that mammary glands in the D-galactose-induced aging model mimic natural aging in terms of pathological changes, epithelial cell composition, and mammary stem/progenitor cell function. These changes are accompanied by elevated inflammatory responses both systemically in the blood and locally in the mammary glands, which is similar in mice who age naturally. Our study for the first time evaluated the mammary glands and mammary stem/progenitor function in a D-galactose-induced aging model in rodents, and our findings suggest that D-galactose treatment can be used as a surrogate to study the role aged stem/progenitor cells play in breast tumorigenesis.